2018
DOI: 10.1101/258111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fatherhood alters gene expression within the MPOA

Abstract: Abstract:Female parenting is obligate in mammals, but fathering behavior among mammals is rare.Only 3-5% of mammalian species exhibit biparental care, including humans, and mechanisms of fathering behavior remain sparsely studied. However, in species where it does exist, paternal care is often crucial to the survivorship of offspring. The present study is the first to identify new gene targets involved in the regulation of fathering behavior in a biparental species using RNA sequencing. In order to determine t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Perhaps most interesting is the overlap in gene expression change induced by pairing in both male seahorses (this study) and the MPOA and NAcc of male prairie voles 61 . The RRHO approach allows for an unbiased comparison between genes of interest that are found in different regions and/or species 16,63,64 .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Perhaps most interesting is the overlap in gene expression change induced by pairing in both male seahorses (this study) and the MPOA and NAcc of male prairie voles 61 . The RRHO approach allows for an unbiased comparison between genes of interest that are found in different regions and/or species 16,63,64 .…”
Section: Discussionmentioning
confidence: 91%
“…It is designed to be used to compare gene expression both between species and between studies, 63,64 and has recently been used to compare gene expression in multiple monogamous species in order to suggest genes that may be conserved across phylogenies 16 . In this analysis, we compared differentially expressed genes in lined seahorses to data from a previous study where we examined gene expression in male prairie voles that had experienced one of three parenting conditions: virgin males, paired males and males with fathering experience 61 . We also compared both seahorse and prairie vole MPOA gene expression data to gene expression from a previously published prairie vole study, 62 which contained publicly available data from the NAcc of male prairie voles that had experienced 3 weeks of cohabitation with a partner (3 W) 62 compared to males that cohabitated with a same‐sex sibling (SN).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, two studies that compared paternal and non-paternal male California mice found no difference in morphometry of the medial preoptic region of the hypothalamus (Gubernick et al, 1993;Horrell et al, 2019). However, this does not preclude morphometric differences between father and non-fathers in other areas of the hypothalamus, especially given that parenthood induced changes in hypothalamic cells include an upregulation of gene expression related to plasticity (Seelke et al, 2018). Overall, the hypothalamus appears to be an important structure underlying both maternal and paternal caregiving.…”
Section: And B)mentioning
confidence: 99%